Stakeholders’ views and experiences on implementing new diagnostics in primary care to support management of community-acquired acute respiratory tract infections: a qualitative study - Hoste, Melanie Eugenie; Colman, Elien; Wanat, Marta; Hayward, Gail; Tissier, Jean-Louis; Postma, Maarten; Goossens, Herman; Anthierens, Sibyl; Tonkin-Crine, Sarah; , on behalf of the VALUE-Dx study team (Frontiers in Public Health, 2023)
The majority of antibiotics are prescribed in primary care for respiratory tract infections. Point-ofcare tests (POCTs) for the management of community-acquired acute respiratory tract infections (CA-ARTI) have been developed to help optimise antibiotic prescribing. Whilst some countries in Europe have adopted these tests in primary care settings, most have not. Stakeholders, such as policymakers, regulators, the diagnostic industry, and scientific associations, have roles in the implementation of new diagnostics in primary care. The aim of this study is to explore these stakeholders' views and experiences, and identify areas of unmet need relating to POCT implementation.Stakeholders were recruited using purposive sampling and snowballing. Between March 2021 and May 2022, semi-structured interviews were conducted online with stakeholders in Belgium, the UK and from European Union (EU) -level organisations. Interviews were audio recorded and transcribed verbatim. Transcripts were analysed inductively and deductively using thematic analysis.Twenty-six stakeholders participated: eleven from EU-level organisations, seven from Belgium, and eight from the UK. Five themes were identified. Stakeholders felt a balance of top-down and bottomup approaches were an optimal strategy to the implementation of POCTs. Stakeholders stressed the need to engage with clinicians to act as champions for tests to help raise awareness and generate new evidence on how tests are used. Whilst acknowledging the potential of POCTs for improving patient outcomes and impacting antibiotic prescribing behaviour, some raised concerns on how tests would be used in practice and wished to see national data on effectiveness. COVID-19 catalysed the use of tests, but stakeholders were pessimistic that processes for approving diagnostics during the pandemic would be replicated in the future.Stakeholders provided recommendations for research and practice. Robust reimbursement policies could alleviate financial burden from clinicians and patients, encouraging practices to adopt POCTs. Industry is likely to benefit from engaging as early on as possible with other stakeholders. Due to uncertainty amongst stakeholders on the impact of POCTs on antibiotic prescribing, further evidence is needed to understand how practices adopt POCTs and the implications for stewardship. Monitoring how POCTs are used can inform future guidelines on successful diagnostic implementation.